2020
DOI: 10.3390/app10124126
|View full text |Cite
|
Sign up to set email alerts
|

The Stabilization of Liquid Smoke through Hydrodeoxygenation Over Nickel Catalyst Loaded on Sarulla Natural Zeolite

Abstract: Constituents of liquid smoke possess a huge potential to be converted as value-added chemicals, such as flavoring, antiseptics, antioxidants, or even fossil oil substitutes. However, liquid smoke instability, led by the presence of oxygenate compounds, is an obstacle for further utilization and processing. On the other hand, catalyst efficiency in hydrodeoxygenation (HDO) remains challenging. Sarulla natural zeolite (Z), with abundant availability, has not been comprehensively investigated in the catalytic per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Low metal impurities were present on the zeolite, which was due to the activation by acid prior to modification . Furthermore, 15.88% of carbon was detected in zeolite, and this condition was also reported by Gea et al which reported that Sarulla natural zeolite had a considerable amount of carbon (20.27–23.25%). According to Table , there was an increase in the nickel content up to 10.59%, which indicated that nickel had been successfully impregnated on the zeolite.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Low metal impurities were present on the zeolite, which was due to the activation by acid prior to modification . Furthermore, 15.88% of carbon was detected in zeolite, and this condition was also reported by Gea et al which reported that Sarulla natural zeolite had a considerable amount of carbon (20.27–23.25%). According to Table , there was an increase in the nickel content up to 10.59%, which indicated that nickel had been successfully impregnated on the zeolite.…”
Section: Resultssupporting
confidence: 86%
“…The unmodified zeolite catalyst, as shown in Figure a, had a bulky structure with irregular plates. This appearance was consistently reported by Gea et al when preparing Sarulla natural zeolite and activated by acids. Another study also reported that natural zeolite had a granular structure .…”
Section: Resultsmentioning
confidence: 99%
“…Hydrochloric acid causes the release of aluminum species which is outside and within the zeolite framework. Other metals that can dissolve in HCl also come out with aluminum [27]. The same thing happened to zeolites after calcination and oxidation.…”
Section: Cristallinity Analysismentioning
confidence: 85%
“…The results are summarized in Table 1. The findings of the study by Gea et al (2020) were used as a comparison for the SNZ catalyst prior to the addition of metal oxides. After being loaded with metal oxides, the ZrO2/SNZ catalyst displayed several compositional changes, including an increase in the percentage of Si, Al, and the appearance of Zr metal.…”
Section: Morphology and Composition Of Catalystmentioning
confidence: 99%